The Heavenly Jerusalem and the Monk in Syriac Ascetic Literature - Popa, Cătălin-Ştefan ca. 20./21. Jh. (2025)
Syriac literature, particularly monastic texts, often grapples with the tension between the Earthly and Heavenly Jerusalems, with the latter representing the ultimate goal. The “Heavenly Jerusalem” is envisioned as the final destination for the righteous and the realm in which Divine joy is fully realized. It reflects Christians’ aspiration to be accepted into this divine realm after transitioning from physical life to spiritual existence in the afterlife. Syriac monastic authors encourage Christians to experience a foretaste of the Heavenly Jerusalem even in this life through practices such as meditation and prayer. We will examine how these authors portray this mystical residence and whether it is perceived as a temporary spiritual City accessible to monks or as the eternal Heavenly City, the ultimate resting place for souls following death and judgment. Additionally, we should investigate how ascetic practices, meditation, fasting, prayer, and mystical experiences in this world can offer glimpses of the Heavenly Jerusalem and consider the role of the inner spiritual self in this transformative process.